2022
DOI: 10.1007/s11538-021-00983-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Evaluation of the Joint Prevention and Control Mechanism for Curbing COVID-19 in Wuhan

Abstract: The spread of COVID-19 in Wuhan was successfully curbed under the strategy of “Joint Prevention and Control Mechanism.” To understand how this measure stopped the epidemics in Wuhan, we establish a compartmental model with time-varying parameters over different stages. In the early stage of the epidemic, due to resource limitations, the number of daily reported cases may lower than the actual number. We employ a dynamic-based approach to calibrate the accumulated clinically diagnosed data with a sudden jump on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In terms of quality control management, continuous improvement measures are proposed for problems, and continuous improvement is implemented to form a virtuous circle. [13][14][15] In terms of effective communication, to ensure that all communication can be fed back to the people for the first time, the reported problems are solved in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of quality control management, continuous improvement measures are proposed for problems, and continuous improvement is implemented to form a virtuous circle. [13][14][15] In terms of effective communication, to ensure that all communication can be fed back to the people for the first time, the reported problems are solved in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the current COVID-19 prediction tools are mainly of the following types: Models based on kinetic (or dynamics) modeling, which further clarify the pattern of changes in the number of a specific population by dividing the population into Susceptible (S) , Infected (I) , Recovered (R) compartments, etc., and defining the transition relationships among them through several differential equations. Since the onset of the COVID-19 epidemic, multi-generational kinetic models have emerged, whose evolution route could be summarized as: SIR→SEIR [ 26 ], SLIR [ 27 ] (considering close contacts or the latent) → SEI A IR [ 28 ] (considering asymptomatic infected persons), SAHQD [ 19 ] (considering quarantine policies) → SEIRMH [ 29 ], SEPIAHR [ 30 ] (considering medical-related factors) → SCUAQIHMRD [ 31 ] (considering COVID-19 hierarchical treatment). Time series analysis.…”
Section: Literature Reviewmentioning
confidence: 99%
“… N.P. Wuhan, China [ 31 ] SEPIAHR model (Susceptible, exposed, pre-symptomatic infectious, ascertained infectious, unascertained infectious, isolation in hospital and removed N.P. N.P.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By the theory of asymptotically periodic semi-flow (see (Zhao 2017, Theorem 3.2.1)), it can be concluded that…”
Section: Lemma 32mentioning
confidence: 99%